O ensino do handebol a partir de uma proposta híbrida: contribuições do teaching games for understanding e do sport education - Mota Júnyor, Jorge Luiz Rodrigues (2020)
It is understood that Physical Education is an area of knowledge responsible for giving pedagogical treatment to various themes of body culture, among them, sport. However, despite the advances in discussions about the teaching of sport, we are still frequently faced with realities in which its teaching still takes place in a traditional way, centered on the teacher and with an emphasis on technical learning. Against this perspective, we believe that sport should be approached differently through a process that goes beyond the teaching of technical gesture, seeking to meet broader educational purposes that imply the acquisition of an ability to play smart as well as understand the sport in a broader way, collaborating for an omnilateral formation. In turn, this work had the purpose of identifying and discussing the limits and possibilities of using a hybrid teaching proposal, which included principles of the Teaching Games for Understanding (TGfU) and Sport Education Model (SEM) teaching models in teaching of Handball. Both models, each in their own way, share the idea that the sport teaching process should be student-centered. TGfU is dedicated to the perspective of learning technical-tactical content using the manipulation of the game as a tool based on the principles of proper choice of the game, modification by representation, modification by exaggeration and adjustment of tactical complexity. SEM, in turn, presents itself as a teaching model governed by principles that are structured and articulated in the perspective of creating a learning atmosphere rich in elements inherent to the sports scene. This time, this scenario will consist of experiences and learning proper to institutionalized sport, however under an adequate formative perspective that contemplates the demands of human formation and significant appropriation of the sport. In view of this previous exposure on the models, we believe that they complement each other while a hybrid proposal (TGfU + SEM) tends to enhance the teaching of sport. Thus, based on action research, this study (conducted by the planning and application of a didactic unit based on the hybridity of the models presented) was carried out over 17 meetings, in a 9th grade class of elementary school in a public school in the city. State Educational Network of Tocantins, in the city of Gurupi - TO. Interviews were conducted, in and out, with the conducting teacher and questionnaires with students, also in two moments (entrance and exit). Audio records were made by the researcher at the end of some meetings, which were transcribed to compose the field diary. Filming of the classes was also made, which, together with the interviews, the questionnaires and the field notebook, composed the objects of observation and analysis of this study. Thus, the analysis of the data regarding the implementation of the proposal allowed us to show significant advances in the learning of technical-tactical as well as behavioral aspects and an appropriation of a broader knowledge of the Handball modality. The observed progress reinforces the relevance of the hybrid model, however we observed that some obstacles in the implementation of the model pose as tangible challenges to the teacher and, also, the need for more research that will collaborate to consolidate a consistent and viable field of knowledge when adopted in the school reality, mainly in the context of Brazilian public schools.